PENGARUH BIAYA PRODUKSI DAN BIAYA TENAGA KERJA TERHADAP LABA BERSIH PADA PERUSAHAAN KELAPA SAWIT YANG TERDAFTAR DI BURSA EFEK INDONESIA - Fajar Allam Syah; Johandri Iqbal; Pramesti Nurul Adinda (LP2M Politeknik Jambi, 2025)
The role of production costs and labor costs greatly influences the survival of the company in its operations. The use of these two factors will provide an illustration that the effectiveness of the use of production costs and labor costs will be directed at increasing and decreasing the company's net profit. The purpose of this study is to prove the effect of production costs and labor costs on net profit in oil palm plantation companies. This study takes time series data in the form of financial reports for the period 2020-2023. The analysis tool used is the SPSS version 25 program with data analysis used in this study, namely the classical assumption test and multiple linear regression and hypothesis testing using simultaneous tests (F) and partial tests (t) with the intention of determining the effect of independent variables on the dependent variable at a confidence level of 12.4% (à = 0.124). The results of this study indicate that production costs and labor costs simultaneously affect net profit. Production costs partially have no effect on net profit. Labor costs partially affect net profit.